2021
DOI: 10.2147/dmso.s299060
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Estimated Pancreatic Steatosis is Associated with Carotid Plaque in Type 2 Diabetes Mellitus Patients: A Cross-Sectional Study from China

Abstract: To explore potential effects of pancreatic fat content measured by computed tomography (CT) on carotid plaque in patients with type 2 diabetes mellitus (T2DM). Methods: T2DM patients who underwent an un-enhanced CT scan of the upper abdomen and ultrasound of the carotid artery were enrolled. The patients were divided into a non-plaque group and a plaque group (including hypoechoic plaque subgroup and non-hypoechoic plaque subgroup). The CT attenuation of pancreas and spleen were measured. Pancreas-to-spleen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…35,36 Recent clinical studies confirm this observation, where fatty change of the pancreas was associated with the thickening of epicardial adipose tissue and aortic intimamedia (markers of subclinical atherosclerosis). 37 There have also been reports of a significantly increased carotid intima-media thickness, 9,38 a higher prevalence of carotid artery plaque and vascular stiffness, 10,39 as well as coronary and carotid calcification in the presence of fatty change of the pancreas. 40 Similarly, CGM metrics have been shown to be associated with cardiovascular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Recent clinical studies confirm this observation, where fatty change of the pancreas was associated with the thickening of epicardial adipose tissue and aortic intimamedia (markers of subclinical atherosclerosis). 37 There have also been reports of a significantly increased carotid intima-media thickness, 9,38 a higher prevalence of carotid artery plaque and vascular stiffness, 10,39 as well as coronary and carotid calcification in the presence of fatty change of the pancreas. 40 Similarly, CGM metrics have been shown to be associated with cardiovascular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Thus, it is clear that conventional risk factors have some effect on the relationship between fatty pancreas and atherosclerosis. In addition, the study populations in previous studies mainly involved patients with NAFLD 6 , 7 and T2DM, 5 , 9 whereas the participants selected for this study were patients with overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Moreover, a Chinese study suggested that CT-estimated pancreatic fat content correlated with carotid plaque in patients with T2DM. 9 Yet another study found a direct link between carotid artery calcification and pancreatic fat. 10 However, the direct connection between NAFPD and atherosclerosis became weaker after adjusting for confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…First, since this was a cross‐sectional study, we cannot make assumptions of causality. Although we believe abnormal components of the lipid panel (in particular, high remnant cholesterol) may have implications in the development of IPFD and that increased IPFD may have a role in the development of cardiovascular diseases, 9,10 longitudinal studies would be required to confirm the presence of any causal relationships. Second, while several genetic disorders (e.g., familial chylomicronaemia syndrome) are associated with abnormalities of the lipid panel, our study did not analyse genetic factors 31 .…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive meta‐analysis of clinical outcomes from 24 studies revealed that people with fatty pancreas had a 67% significantly increased risk for arterial hypertension 8 . Also, an earlier clinical study found that fatty pancreas was significantly associated with a 3.1‐times higher chance of carotid atherosclerosis in non‐obese people, 9 whereas a recent clinical study showed that fatty pancreas was significantly associated with a 2.8‐times higher chance of carotid plaques in people with type 2 diabetes 10 . Further, an autopsy study reported that fatty pancreas was significantly associated with severe atherosclerosis 11 …”
Section: Introductionmentioning
confidence: 99%